2000
DOI: 10.1080/003655400750044917
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV Type 1 Infection, Associated Clinical Features and Mortality among Hospitalized Children in Dar es Salaam, Tanzania

Abstract: The aim of this study was to determine the prevalence of HIV-1 infection, the clinical spectrum of HIV-1-associated conditions and HIV-1-associated mortality among children hospitalized in the medical paediatric wards at Muhimbili Medical Centre (MMC), Dar es Salaam, Tanzania. All children admitted to the medical paediatric wards of MMC between August 1995 and January 1996 were eligible for the study. Testing for HIV antibodies was done using 2 consecutive enzyme linked immunosorbent assays (ELISAs). ELISA-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is important as malnutrition has a major impact on the outcome of HIV disease as it not only increases mortality [12, 13] but also results in an impaired response to antiretroviral therapy [14]. Rajasekaran et al showed that children who were severely malnourished at baseline, had a hazard ratio of 6.7 (0.9–49.4) for mortality after initiation of ART, compared to children who were normally nourished [14].…”
Section: Discussionmentioning
confidence: 99%
“…This is important as malnutrition has a major impact on the outcome of HIV disease as it not only increases mortality [12, 13] but also results in an impaired response to antiretroviral therapy [14]. Rajasekaran et al showed that children who were severely malnourished at baseline, had a hazard ratio of 6.7 (0.9–49.4) for mortality after initiation of ART, compared to children who were normally nourished [14].…”
Section: Discussionmentioning
confidence: 99%
“…[3] The World Health Organization (WHO) advocates a public health approach to ART, recognising the potential role of plasma HIV-1 RNA testing but recommending clinical and immuno logical monitoring in resource-constrained countries such as Tanzania. [4,5] It has been shown that there are challenges related to the use of clinical and immunological parameters to detect virological failure in adults receiving ART. The delay in recognition may result in increased acquisition of HIV drug-resistant mutations as well as increased morbidity and mortality.…”
mentioning
confidence: 99%
“…Despite the efforts made, in low-income countries, many infants continue to be infected each year and often die prematurely. Infant HIV mortality rate, in the absence of treatment, is the greatest during the early years of life [1,2]. In low-income countries, HIV/AIDS infected children care interventions coverage remains very low, specifically in rural areas.…”
Section: Introductionmentioning
confidence: 99%